The Ratiometric Transcript Signature MX2/GPR183 Is Consistently Associated With RTS,S-Mediated Protection Against Controlled Human Malaria Infection - Du, Ying; Thompson, Ethan G.; Muller, Julius; Valvo, Joseph; Braun, Jackie; Shankar, Smitha; van den Berg, Robert A.; Jongert, Erik; Dover, Drew; Sadoff, Jerald; Hendriks, Jenny; Gardner, Malcolm J.; et al. (Frontiers in Immunology, 2020)
The RTS,S/AS01 vaccine provides partial protection against Plasmodium falciparum infection but determinants of protection are unclear. Previously, anti-circumsporozoite protein (CSP) titers and blood RNA signatures were associated with RTS,S/AS01 efficacy against controlled human malaria infection (CHMI). By analyzing host blood transcriptomes from five RTS,S vaccination CHMI studies, we demonstrate that the transcript ratio MX2/GPR183, measured one day after third immunization, discriminates protected from non-protected individuals. This ratiometric signature provides information that is complementary to anti-CSP titer levels for identifying RTS,S/AS01 immunized people who developed protective immunity and suggests aroles for interferon and oxysterol signaling in the RTS,S mode of action.